Analisis Persepsi dan Preferensi Konsumen terhadap Permintaan Produk Jamu XYZ di Kota Bogor - Sheren Inggrid Julianty; Fiqha Savara Al Hikmah; Haikal Fikri Ikhwan; Luqman Kurniawan Ardi; Dhimas Pradythia K.W; Rasidin Karo Karo Sitepu; R Thoifatul Munawwaroh (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study analyzes the influence of price perception, product differentiation, brand equity, and consumption preferences on the demand for Jamu XYZ in Bogor City amid increasing public interest in healthy lifestyles and traditional herbal beverages. A quantitative explanatory approach was employed using a survey method. Data were collected through questionnaires distributed to 50 consumers who had consumed Jamu XYZ and were selected using purposive sampling. The data were analyzed using descriptive statistics, the Fishbein attitude model, multiple linear regression, validity and reliability tests, and classical assumption tests. The results indicate that consumers generally hold positive perceptions of Jamu XYZ, particularly regarding its health benefits, packaging, and price suitability. Consumer preferences were also categorized as high, showing that product attributes such as health benefits, brand image, and packaging are important considerations in purchasing decisions. Fishbein analysis revealed an overall positive consumer attitude toward the product, with packaging identified as the most influential attribute. Multiple regression analysis showed that price perception has a positive and significant effect on product demand, while consumption preferences also contribute positively to demand. Conversely, product differentiation and brand equity do not significantly affect demand. The coefficient of determination suggests that other external factors also influence consumer demand. These findings highlight the importance of maintaining competitive pricing strategies and aligning product attributes with consumer preferences to increase demand and strengthen the competitiveness of herbal beverage products in the market.